Mitochondria The Dynamic Organelle - Schaffer, Stephen W.; Suleiman, M. Saadeh (Advances in Biochemistry in Health and Disease, 2007)
About the Series: Advances in Biochemistry in Heath and Disease presents state-of-the-art discussions in cutting-edge biochemical research, offering exciting developments that impact healthcare and disease research. Volumes in the series focus on cross-disciplinary biomedical research and examine various topics in biochemistry, cell biology, molecular biology, and biomedicine. Mitochondria: The Dynamic Organelle Mitochondria: The Dynamic Organelle focuses on the function of the mitochondria and the organelle's role in cellular pathology. While the traditional function of the mitochondria is metabolic, recent cutting-edge studies have uncovered a central role for mitochondria in cell signaling, cell survival and cell death. Mitochondria: The Dynamic Organelle presents examples of crosstalk between the mitochondria and the rest of the cell, which serve a regulatory role by modulating the levels of key metabolites, ions and oxidants or the activities of key rate-controlling enzymes. Detailed descriptions of the involvement of membrane receptors, channels, enzymes and metabolites in the cardioprotective mechanisms of the mitochondria are provided. This volume also discusses the death pathways that are initiated by the mitochondria. Novel therapeutic interventions are proposed which interfere with the death cascades, thereby rescuing the cell from mitochondria-linked apoptosis and necrotic oncosis. Mitochondria: The Dynamic Organelle is a timely contribution that addresses the reemergence of the mitochondria as a key player in cellular function and pathology. Key topics: Amino acid metabolism Carbohydrate and lipid metabolism Citric acid cycle regulation and metabolite transport Electron transport and oxidative phosphorylation Ischemic preconditioning Mitochondrial apoptosis Mitochondrial DNA damage Mitochondrial permeability transition Mitochondrial ion transporters Necrotic oncosis and mitochondrial dysfunction Peroxisome proliferators-activated receptors (PPARs) Mitochondria: The Dynamic Organelle is essential reading for researchers, molecular and cellular biologists, biochemists, physiologists and pathologists. About the Editors: Stephen W. Schaffer has been a professor of Pharmacology at the University of South Alabama, College of Medicine since 1988. He received training in mitochondrial function from the Johnson Research Foundation at the University of Pennsylvania. His research focuses on the effects of diabetes and angiotensin II on the heart, with a particular emphasis on the effects of mitochondrial DNA damage on the cardiomyocyte. He is a recipient of the Vincenzo Penagia Distinguished Scientist Award and is a fellow of the International Academy of Cardiovascular Sciences. He serves on the editorial board of Amino Acids and Molecular and Cellular Biochemistry and is editor of several books. M.-Saadeh Suleiman is currently a Professor of Cardiac Physiology at the Faculty of Medicine and Dentistry, University of Bristol. He joined the Department of Physiology in Bristol in 1988 and was one of the founders of the Bristol Heart Institute. His research is focused on myocardial protection including the role of mitochondria, and had significant impact on cardiac surgery where he was a member of the team that received the UK Hospital Doctor Award in 2005 for innovative surgery. He was a recipient of a Fulbright Fellowship and in 2003 was awarded a DSc in Physiology from the University of Bristol. He was elected twice to the executive committee of the British Society of Cardiovascular Research (1998-2004).